Buttiauxella phytase maintains growth performance in broilers fed diets with reduced nutrients under a commercial setting - Y. Dersjant-Li; K. Van de Belt; C. Kwakernaak; L. Marchal (Journal of Applied Animal Nutrition)
The effect of down specifying nutrients in diets supplemented with Buttiauxella spp. phytase was studied in a commercial trial. Three treatments were tested with five replicate groups, each containing 700, one-day-old straight run Ross 308 broilers. Birds were fed pelleted diets from days 0-42 in four phases: starter (days 0-10); grower (days 11-21); finisher 1 (days 22-35) and finisher 2 (days 36-42). A nutritionally adequate, unsupplemented, positive control (PC) diet based on wheat, corn and soybean meal was compared against two down specified, negative control (NC) diets containing Buttiauxella phytase supplemented at 500 or 1000 FTU/kg. The reduction level was 0.134 and 0.159% unit for digestible phosphorus, 0.164 and 0.189% unit for calcium, 0.03 and 0.04% unit for sodium, 0.283 and 0.309 MJ/kg for nitrogen corrected apparent metabolizable energy in all phases and variable digestible amino acids in different phases, respectively for the diets containing the phytase at 500 and 1000 FTU/kg. An unsupplemented NC diet was not included, as it would have caused welfare and health issues. Weight gain and mortality-corrected feed conversion ratio for birds receiving phytase at either inclusion levels were equivalent to the PC group. Feed intake was increased by 500 FTU/kg phytase (P<0.05) during 0-21 d vs PC. Including 1000 FTU/kg phytase reduced water intake vs PC at 0-42 d and water-to-feed intake ratios, after the starter phase (P<0.05). Carcass yield in birds supplemented with either phytase level was not different from PC. Tibia ash was unaffected by treatment. Estimated feed costs (inclusive of phytase) were lower in supplemented than un-supplemented (PC) diets, by 10.0 to 13.7 €/ton diet. The trial demonstrated that reducing nutrient specifications of diets supplemented with Buttiauxella phytase maintained growth performance, lowered feed costs, with production benefits maximised at inclusion levels of 1000 FTU/kg.